Implementation of the Lourenço Filho Test for the Assessment of Reading and Writing Skills in Second Grade Students - Chávez Rosero, Jairo Ricardo; Carpio Calvache, Tiffany Leonela; Quintana Narváez, Dayra Cristina (Revista Ecos de la Academia, 2025)
This research aims to diagnose and demonstrate how the application of the Lourenço Filho Maturity Test for Learning Literacy contributes to determining the necessary aptitudes to achieve effective reading and writing maturity in children aged 5 to 6 years. The study was conducted with 291 second-grade students from central schools in the city of Tulcán (180 girls and 111 boys). The results indicate that, at the individual level, the projection of learning to read and write is in chronological-academic balance (6 months to 1 academic year); however, the group-level results show that reading comprehension requires reinforcement due to the lack of adequate support in the development of activities that foster the maturation of skills involved in reading and writing. These findings were obtained through the in situ application of the test and its subsequent analysis using descriptive statistics based on median and standard deviation formulas. The study encourages first- and second-grade teachers to use the test as a pedagogical tool in early teaching and learning of language arts.
Keywords: Learning; Reading Comprehension; Assessment; Reading; Educational Psychology